2020
DOI: 10.1101/2020.10.29.359380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CK2 alpha prime and alpha-synuclein pathogenic functional interaction mediates synaptic dysregulation in Huntington’s disease

Abstract: Huntington′s Disease (HD) is a neurodegenerative disorder caused a polyglutamine expansion in the HTT protein. This mutation causes HTT misfolding and aggregation, preferentially affecting neurons of the basal ganglia. Other aggregation-prone proteins like alpha-synuclein (α-syn), mostly associated with Parkinson′s disease (PD), has recently been involved in motor deficits in HD, but its mechanism of action is unknown. Here we showed that α-syn serine 129 phosphorylation (α-syn-pS129), a posttranslational modi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 141 publications
(370 reference statements)
6
11
0
Order By: Relevance
“…However, this alteration most likely reflects changes in tCr. Lower NAA and higher Ins, which are considered markers of neurodegeneration, were previously reported in more severe HD mouse models such as the R6/2 (12 weeks) (Tkác et al, 2007), homozygous zQ175 (Tg/Tg) (12 months) (Peng et al, 2016) and in older zQ175 Tg/0 (22 months) (Tkác et al, 2007;Heikkinen et al, 2012;Peng et al, 2016;Yu et al, 2020). Therefore, these data suggests that tNAA and Ins may reflect substantial neurodegeneration in advanced disease.…”
Section: Longitudinal In Vivo 1 H-mrs Captures Genotype and Age-specific Striatal Neurochemical Changes In The Zq175 Hd Mouse Modelsupporting
confidence: 69%
See 4 more Smart Citations
“…However, this alteration most likely reflects changes in tCr. Lower NAA and higher Ins, which are considered markers of neurodegeneration, were previously reported in more severe HD mouse models such as the R6/2 (12 weeks) (Tkác et al, 2007), homozygous zQ175 (Tg/Tg) (12 months) (Peng et al, 2016) and in older zQ175 Tg/0 (22 months) (Tkác et al, 2007;Heikkinen et al, 2012;Peng et al, 2016;Yu et al, 2020). Therefore, these data suggests that tNAA and Ins may reflect substantial neurodegeneration in advanced disease.…”
Section: Longitudinal In Vivo 1 H-mrs Captures Genotype and Age-specific Striatal Neurochemical Changes In The Zq175 Hd Mouse Modelsupporting
confidence: 69%
“…Previous studies in patients with different spinocerebellar ataxias (SCAs) presenting different degrees of synapse loss proposed that neurochemical alterations measured by MRS may reflect changes in synaptic function or density (Öz et al, 2011a;Joers et al, 2018). Consistently, a recent MRS study in aged zQ175 mice showed that key striatal neurochemical alterations paralleled changes in T-S synapses (Yu et al, 2020), highlighting the potential use of MRS as a tool to monitor synapse density. However, the relationship between neurochemical alterations and synaptic density has not been directly assessed thus far.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations